2022
DOI: 10.1038/s41467-022-28189-9
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Huanglongbing is a pathogen-triggered immune disease that can be mitigated with antioxidants and gibberellin

Abstract: Huanglongbing (HLB) is a devastating disease of citrus, caused by the phloem-colonizing bacterium Candidatus Liberibacter asiaticus (CLas). Here, we present evidence that HLB is an immune-mediated disease. We show that CLas infection of Citrus sinensis stimulates systemic and chronic immune responses in phloem tissue, including callose deposition, production of reactive oxygen species (ROS) such as H2O2, and induction of immunity-related genes. The infection also upregulates genes encoding ROS-producing NADPH … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 85 publications
4
85
0
Order By: Relevance
“…Previous research demonstrated that ROS was elevated in citrus leaves following C Las infection (Ma et al, 2022; Pitino et al, 2017). However, ROS has not been quantified in infected seed vasculatures, where our results indicated that bacteria are present in large numbers.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research demonstrated that ROS was elevated in citrus leaves following C Las infection (Ma et al, 2022; Pitino et al, 2017). However, ROS has not been quantified in infected seed vasculatures, where our results indicated that bacteria are present in large numbers.…”
Section: Resultsmentioning
confidence: 94%
“…This corresponded with a lower expression of the CsCalS and CsRBOH genes. Previously it was shown that callose and ROS metabolism increase in infected plants (Ma et al, 2022; Pitino et al, 2017; Granato et al, 2019), but these observations were made in the leaf tissue, where C Las levels are low. Our results suggest that these increases include both the activation by the host and inhibition by the pathogen, but because the pathogen is absent from most SE in the leaf, the net effect is an increase.…”
Section: Discussionmentioning
confidence: 97%
“…Downregulation of a few HSPs has been reported in HLB susceptible citrus after CLas infection 46,[61][62][63] , while upregulation of them was putatively related to enhanced HLB tolerance 46 . Ma et al (2022) inferred the accumulation of reactive oxygen species (ROS) to be caused by chronic immune responses in the phloem tissue 64 . However, there is no proof that CLas could be recognized by citrus within the phloem, which is a prerequisite for inducing immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced NPR1 dependent defense 41,42 or high-level antimicrobial peptide expression 4345 ; B. Promoted protein and cellular homeostasis due to upregulation of molecular chaperones (mainly heat shock proteins); C. Inhibition of programmed cell death by high-level of antioxidant metabolites or enhanced detoxication pathways 46,48,64 ; D. Increased functional phloem ratio from novel high phloem regeneration rate 15,49 .…”
Section: Figure Legendsmentioning
confidence: 99%
“…Recent research indicates that elevated levels of manganese (Mn) promote better tree response to the effects of HLB increasing citrus tree lifespan ( Morgan et al, 2016 ; Zambon et al, 2019 ). Sufficient Mn in the rhizosphere is critical for scavenging ROS ( Alscher et al, 2002 ), which is known to be produced extensively in C Las-damaged cells ( Ma et al, 2022 ). Although many nutrients can mitigate symptoms of HLB-affected trees, the mechanisms of how these nutrients trigger citrus defenses are still unclear and warrant investigation.…”
Section: Host Defense Triggered By Agentsmentioning
confidence: 99%